2006
DOI: 10.2337/diacare.29.01.06.dc05-0862
|View full text |Cite
|
Sign up to set email alerts
|

A Single Factor Underlies the Metabolic Syndrome

Abstract: OBJECTIVE -Confirmatory factor analysis (CFA) was used to test the hypothesis that the components of the metabolic syndrome are manifestations of a single common factor. RESEARCH DESIGN AND METHODS-Three different datasets were used to test and validate the model. The Spanish and Mauritian studies included 207 men and 203 women and 1,411 men and 1,650 women, respectively. A third analytical dataset including 847 men was obtained from a previously published CFA of a U.S. population. The one-factor model include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
85
2
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 40 publications
8
85
2
4
Order By: Relevance
“…It has been demonstrated that using two or more measures for the same trait results in the extraction of more factors than really exist [14]. Similarly, our results show that TG and HDL-C tend to cluster together under a separate factor instead of loading on a common factor, maybe because among studied variables, the correlation coefficient between TG and HDL-C was among the highest coefficients.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…It has been demonstrated that using two or more measures for the same trait results in the extraction of more factors than really exist [14]. Similarly, our results show that TG and HDL-C tend to cluster together under a separate factor instead of loading on a common factor, maybe because among studied variables, the correlation coefficient between TG and HDL-C was among the highest coefficients.…”
Section: Discussionsupporting
confidence: 63%
“…This phenomenon can be a result of the fact that number and nature of components in different studies has been chosen apparently arbitrarily. Since factor analysis extracts factors due to the interrelatedness of measured variables, using two or more measures for the same trait (e.g., systolic blood pressure [SBP] and diastolic blood pressure) leads to find more factors than expected [14].…”
Section: Introductionmentioning
confidence: 99%
“…The fit of the four-factor model (Model 3) was found to be plausible (although fit was not exact) and this fit was significantly better than the fit of the two-factor oblique model. The better fit exhibited by the four-factor model appears to be, in part, secondary to the measures of the factors used in the model based on currently published EFA [24] and CFA analysis [25]. Salmenniemi et al, using EFA techniques, produced fourfactor models when the variables of fasting glucose, 120-min glucose, fasting insulin (log), 120-min insulin (log), BMI, waist circumference, HDL-cholesterol, triglycererides (log), systolic blood pressure and diastolic blood pressure were used in their factor analysis [24].…”
Section: Discussionmentioning
confidence: 94%
“…A onefactor solution was obtained if the measures of systolic and diastolic blood pressure were replaced with a mean arterial blood pressure value. Pladevall et al also obtain a one-factor model when they use the following variables to measure their ''metabolic syndrome'' factor: waist circumference, triglycerides/ HDL-cholesterol, homestasis model assessment of insulin resistance (HOMA-IR), and mean arterial blood pressure [25]. Therefore, with no surprise, and as noted by Pladevell et al that variable selection for an EFA or CFA model has a great deal to do with the ultimate fit of the model.…”
Section: Discussionmentioning
confidence: 98%
“…Metabolic syndrome (MetS) is the co-occurrence of multiple metabolic risk factors for type 2 diabetes, cardiovascular disease (CVD), and chronic kidney disease [1,2]. The process begins early in life, long before clinical disease is evident and persists through childhood to adolescence/ adulthood [3,4].…”
Section: Introductionmentioning
confidence: 99%